Hubungan Antara Politik dan Kepemimpinan Islam: Tantangan dan Peluang - Kokom Komariah; Masyitoh; Muhammad Hidayat Nur Wahid; Saeful Bahri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to get to know the concepts, principles and theories of leadership in Islam, explain the leadership process of Rasulullah SAW, understand the implementation of leadership by Rasulullah SAW, explain the challenges of implementing Islamic leadership concepts in Indonesia, encourage the application of Islamic leadership concepts in Indonesia. By using qualitative research methods with a literature study approach. Qualitative research focuses on searching for meaning and describing phenomena in a holistic and natural way. Primary sources are literature about Islamic leadership, while secondary sources are books related to the themes discussed. Indirect data collection techniques were carried out by examining relevant objects, and data analysis using descriptive methods produced the following findings that Leadership in Islam is based on the Al-Qur'an and Hadith, emphasizing piety, justice, trust and deliberation. Key principles include trust, justice, and deliberation. Rasulullah SAW built leadership by focusing the activities of the people at the Nabawi Mosque, uniting the tribes in Medina, and implementing formal and spiritual strategies. He is an example of fair, wise and inspiring leadership, prioritizing the interests of the people. In Indonesia, the challenges of implementing Islamic leadership concepts include cultural diversity, requiring leaders who are sensitive to local values. Leaders must uphold the principles of honesty, fairness and inclusiveness, as well as focus on education, resource management and the protection of human rights